Environmental health effects attributed to toxic and infectious agents following hurricanes, cyclones, flash floods and major hydrometeorological events. (18th August 2019) - Erickson, Timothy B.; Brooks, Julia; Nilles, Eric J.; Pham, Phuong N.; Vinck, Patrick
ABSTRACT: Extreme hydrometeorological events such as hurricanes and cyclones are increasing in frequency and intensity due to climate change and often associated with flash floods in coastal, urbanized and industrial areas. Preparedness and response measures need to concentrate on toxicological and infectious hazards, the potential impact on environmental health, and threat to human lives. The recognition of the danger of flood water after hurricanes is critical. Effective health management needs to consider the likelihood and specific risks of toxic agents present in waters contaminated by chemical spills, bio-toxins, waste, sewage, and water-borne pathogens. Despite significant progress in the ability to rapidly detect and test water for a wide range of chemicals and pathogens, there has been a lack of implementation to adapt toxicity measurements in the context of flash and hurricane-induced flooding. The aim of this review was to highlight the need to collect and analyze data on toxicity of flood waters to understand the risks and prepare vulnerable communities and first responders. It is proposed that new and routinely used technologies be employed during disaster response to rapidly assess toxicity and infectious disease threats, and subsequently take necessary remedial actions.